Luminescent Zinc Fingers: Zn‐Responsive Neodymium Near‐Infrared Emission in Water. Issue 46 (31st July 2017) - Isaac, Manon; Raibaut, Laurent; Cepeda, Céline; Roux, Amandine; Boturyn, Didier; Eliseeva, Svetlana V.; Petoud, Stéphane; Sénèque, Olivier
Abstract: Responsive luminescent probes emitting in the near‐infrared (NIR) are in high demand today for biological applications as they allow for the easy and unambiguous discrimination of autofluorescence. Due to their luminescence properties, lanthanide ions offer an interesting alternative to classical organic fluorescent dyes. This has stimulated the development of lanthanide‐based responsive probes. Nevertheless, responsive probes that can operate in water with NIR‐emitting lanthanide ions are scarce. In this communication, zinc fingers are shown to be versatile scaffolds to elaborate a variety of Zn 2+ ‐responsive probes based on lanthanide emission and featuring desirable properties for the selective detection of Zn 2+ in experimental conditions close to cellular. Of special interest is a NIR‐emitting probe relying on Nd 3+ emission. Abstract : Lighting neodymium with zinc : A family of lanthanide‐based probes elaborated on a zinc finger peptide scaffold shows a selective turn‐on emission response to Zn 2+ in pseudo‐physiological conditions. One of these probes is able to report the presence of Zn 2+ by the near‐infrared emission of neodymium at 1060 nm.